2009
DOI: 10.1111/j.1365-2702.2009.02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of nurses’ smoking cessation interventions: report from a national survey

Abstract: Aims and objectives. To describe the frequency of nurses' delivery of tobacco cessation interventions ('Five A's': Ask, Advise, Assess, Assist, Arrange) and to determine the relationship of interventions to nurses' awareness of the Tobacco Free Nurses initiative. Background. Tobacco cessation interventions can be effectively provided by nurses. The delivery of smoking cessation interventions by healthcare providers is mandated by several organisations in the USA and around the world. Lack of education and reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 50 publications
6
92
2
4
Order By: Relevance
“…Of these, 708 completed the questionnaire. This gives a response rate of 22.6 per cent, which matches that of other comparable studies (48). In 2014, a total of 4 368 public health nurses were working in Norway.…”
Section: Implications the Trainingsupporting
confidence: 68%
“…Of these, 708 completed the questionnaire. This gives a response rate of 22.6 per cent, which matches that of other comparable studies (48). In 2014, a total of 4 368 public health nurses were working in Norway.…”
Section: Implications the Trainingsupporting
confidence: 68%
“…Even though 70% of cancer patients who smoke are motivated to quit smoking, only 56% of physicians recommend that their cancer patients who smoke stop smoking 52 and most oncology providers do not provide smoking interventions beyond advice to quit. 53 Our work 54 and the work of others [55][56][57][58][59] have shown that the major barriers to providers implementing smoking cessation services included lack of expertise and time. Education programs for health care providers as well as dedicated smoking cessation programs would improve tobacco treatment for cancer patients.…”
Section: Discussionmentioning
confidence: 94%
“…Nurses would be well situated to assess and assist with smoking cessation. However, a survey of nurses at 35 magnet-designated hospitals found that cessation interventions were suboptimal (Sarna et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Addressing smoking cessation among current smokers in the survivor population is an important but challenging task (Gritz et al, 2006;McBride & Ostroff, 2003;Patsakham, RipleyMoffitt, & Goldstein, 2009;Sarna et al, 2009). Using the 2005 NHIS, 1,825 cancer survivors responded to questions about smoking status and cessation efforts.…”
Section: Discussionmentioning
confidence: 99%